The Condition of the Diverse Regions of Rural America - E. Robert Stephens (Journal of Research in Rural Education, 1991)
Itis important that policy analysts at the state and federal levels intent on designing fiscal policies for rural schools be especially mindful of the great diversity in rural America. The socioeconomic and political trends impacting different nonmetropolitan regimes at the beginning of the present decade will further complicate the construction of fiscal policies that will stand the tests of both equity and adequacy